Analysis of patient knowledge on interdisciplinary care and self-care in venous leg ulcers - Joanna Michalik; Iwona Grzelak; Dariusz Wolski; Andrzej Stanisławek; Paweł Węgorowski (Kazimierz Wielki University, 2017)
Venous leg ulcer is a chronic disease and is considered a multi-faceted problem. This condition requires care including social, economic, therapeutic, nursing care. Patients with ulceration feel rejection in the environment, lack of acceptance due to odor and secretion from the ulcer. These symptoms lead to partial or complete isolation and withdrawal from life in society. This condition requires interdisciplinary care, and treatment requires a lot of skill, work and sacrifice from the patients.   Objective The aim of the study was to assess knowledge, knowledge of interdisciplinary care and self-care, in the life of each patient with venous leg ulcers. Material and methods The study was conducted among 60 people. The research material was collected at the Międzyleski Hospital in Warsaw in the Department of Dermatology in 2015. Selected research method was questionnaire survey of its own author. Results The survey showed that the phenomenon of interdisciplinary care, is only in the 8% known concept, more knowledgeable are lonely people living in large cities. Self-care does not associate with maintaining wellbeing and health. Respondents have knowledge of who is part of the interdisciplinary team, but they can not determine what the task is. Most respondents confirm that there is little availability for specialists, diagnostics, and that the cost of treatment sometimes exceeds the financial capacity of the sick. Disease significantly influences lifestyle change and triggers negative feelings in them, yet respondents are unable to introduce self-care in everyday life. Discussion It is therefore reasonable to say that the treatment of ulcers should be comprehensive and organized, consistent with the principles of modern medicine, and should be based on procedures and standards.